2019
DOI: 10.1177/1469066719857564
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectral analysis of acetylated peptides: Implications in proteomics

Abstract: Sequence determination of peptides using mass spectrometry plays a crucial role in the bottom-up approaches for the identification of proteins. It is crucially important to minimise false detection and validate sequence of the peptides in order to correctly identify a protein. Chemical modification of peptides followed by mass spectrometry is an option for improving the spectral quality. In silico-derived tryptic peptides with different N-terminal amino acids were designed from human proteins and synthesized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Protonated and sodiated precursors provided abundant b, y, and a ions. In agreement with previous reports [60], MS 2 spectra of acetylated peptides showed higher numbers and significantly more abundant b ions compared to non-acetylated peptides. Protonated peptides in low-energy CID produce b and y ion series.…”
Section: Mass Spectra Of Acetylated Peptide Standardssupporting
confidence: 92%
“…Protonated and sodiated precursors provided abundant b, y, and a ions. In agreement with previous reports [60], MS 2 spectra of acetylated peptides showed higher numbers and significantly more abundant b ions compared to non-acetylated peptides. Protonated peptides in low-energy CID produce b and y ion series.…”
Section: Mass Spectra Of Acetylated Peptide Standardssupporting
confidence: 92%
“…Acetylation of tryptic peptides by a reaction with acetic anhydride is a means of improving the quality of mass spectra by increasing the occurrence and abundance of fragment ions. 27 Although no intentional acetylation was carried out, the presence of these modifications can be attributed to a prolonged contact of the sample with high concentrations of acetate during the SelP purification step followed by acidification with ( ca. 1% formic acid just after tryptic digestion) which could catalyze the observed reaction.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the identified 203 protein N termini with the initiator methionine were corresponding to 248 peptide identification, among which 215 peptides (86.7%) were not found to contain oxidized methionine, while two forms of some peptides both with and without oxidized methionine were identified at the same time. It was reported that N-terminal acetylation of the tryptic peptides could improve the abundance and occurrence of b-ions including b1 ions . Therefore, the % of b1 ions detected from N-terminal acetylated residues was also counted to provide additional information for the N-terminal acetylated peptides.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It was reported that N-terminal acetylation of the tryptic peptides could improve the abundance and occurrence of b-ions including b1 ions. 32 Therefore, the % of b1 ions detected from N-terminal acetylated residues was also counted to provide additional information for the N-terminal acetylated peptides. Their molecular functions and subcellular locations were analyzed using IPA (Ingenuity Pathway Analysis), and we found that these identified proteins were involved in various molecular functions such as cell cycle, gene expression, cell death and survival, molecular transport and cell signaling, and so on.…”
Section: ■ Results and Discussionmentioning
confidence: 99%